Konsentrasi Logam Berat Timbal (Pb) dan Kadmium (Cd) di Perairan Pelabuhan Benoa Denpasar - Doni Samuel Barus; Pande Gde Sasmita Julyantoro; Ni Putu Putri Wijayanti (Program Studi Manajemen Sumberdaya Perairan, Fakultas Kelautan dan Perikanan, Universitas Udayana, 2024)
Benoa Port is one of the public ports as well as a special export fishing port. The existence of transportation activities at Benoa Port is indicated to have an indirect pollution impact on the waters, so that research related to the heavy metal content of lead (Pb) and cadmium (Cd) in water and water quality conditions in the waters of Benoa Port Denpasar is important to do. Water sampling was carried out at Benoa Port, then the samples were analyzed at the Analytical Laboratory of Udayana University from June-July 2023.The tested water samples were taken from 3 points with 3 repetitions at each point. Point 1 is at the port entrance, point 2 is at the port of the fishing town and point 3 is at RTH Taman Segara. Data from the study was obtained that the highest Pb value was at point 2, which was 0.1 mg/l and the Cd value was 0.054 mg/l. At point 3 the Pb value is 0.025 mg/l and the Cd value is 0.018 mg/l, and the lowest is found at point 1 with a Pb value of 0.02 mg/l and a Cd value of 0.016 mg/l. Water quality parameters measured include temperature, pH, Dissolved Oxygen (DO), and Total Dissolve Solids (TDS). The highest temperature value is found at point 2 of 29.8oC while the lowest temperature value is found at point 1 with a value of 28.6oC.